Safe in the Hands of the Interpreter? A Qualitative Study Investigating the Legal Protection of Deaf People Facing the Criminal Justice System in Norway - Kermit, Patrick; Mj, Odd Morten; Olsen, Terje (Disability Studies Quarterly, 2011)
Keywords Criminal justice, Deaf, Sign Language, Interpreting, Profession Abstract Over the last thirty years Deaf people in Norway have obtained extensive rights to sign language interpreting. During this period, a public national interpreting service has been established to cope with the growing demands for interpreters. However, little is known about how this development has influenced interpreting in different contexts. This paper addresses questions concerning the legal protection of deaf people facing the criminal justice system. A central issue of concern is what kind of communicative barriers Deaf people encounter. An empirical study is presented where sixteen strategically recruited informants participated: nine sign language interpreters and seven representatives from the Norwegian criminal justice system. The methodological approach was qualitative, open-ended interviews. The results indicate that Deaf people benefit from the professionalization of the interpreters in many ways. At the same time, as a profession, interpreters have a responsibility for defining their role. It is questionable whether or not interpreters always make professional decisions in deaf people’s best interest.